Teachers’ Effort to Implement Cultural Education and National Character Values through PPKn in Senior High School - Hamid Darmadi (JPKM (Jurnal Pengabdian Kepada Masyarakat) UNTAN, 2019)
This study is titled: Teacher's Efforts to Implement Cultural Education and National Character Values Through Learning West Kalimantan State High School Bengkayang PPKn. The problem in this study is "How Teachers' Efforts to Implement Cultural Education and Nation Character Values Through Learning PPKn in Bengkayang State High School, West Kalimantan Province. This study aims to" obtain objective information and clarity regarding the Implementation of Character Education through learning PPKn in the Learning Process in Bengkayang State High School. This research is reviewed from two benefits, namely theoretical and practical benefits. The population in this study were students and teachers of Bengkayang State High School PPKn. Data collection was carried out using direct communication techniques using a questionnaire as a data collection tool, indirect communication techniques using interview guides to school principals, teachers, and students who were designated as informants. Besides these two tools, observation techniques and documentation techniques are also used. Data processing uses non-metric descriptive statistical techniques with 1) the formula "Percentage" to find out the percentage of success of the PPKn teacher Applying cultural education and national character values. 2) the "Mean" formula to find the average number of school success rates. Implement cultural education and national character values from the School Indicators, Class Indicators, and Student Behavior Indicators. 3) Standard Deviation (SD) formula to find out the highest and lowest levels of each school applying cultural education and national character values. 4) Absorption formula to determine the level of absorption of each school using each School Indicator effect, Class Indicator, and Student Behavior Indicator. The results of this study show that Teachers' Efforts to Implement Cultural Education and Nation Character Values Through Learning PPKn in Bengkayang State High School are in the "Fair" position. The actual score is 90,139, and the ideal score is 182,532, with a percentage level of 49.38%. It is recommended that the Bengkayang State High School Authority instruct the School Principals and PPKn teachers so that in providing learning material they are not in a hurry to get into the subject matter, but instead start the lesson first by instilling Character Education. The Regional Government, through the Office of Education and Culture, needs to collaborate with the School authorities to improve the implementation of Cultural Education and National Character Values in PPKn learning.